Comic drunks, crazy cults, and lovable monsters : bad behavior on American television - Diffrient, David Scott, 1972- (Syracuse, New York : Syracuse University Press, 2022)
"Diffrient explores the ways in which social imaginaries related to "bad behavior" have been humorously exploited over the years through his examination of a broad range of network and cable TV shows across the history of the medium"--
Contemporary TV Comedy: A "Good Place" for "Bad People" -- Part One. TV's Alcoholic Imaginary: Comic Drunks, Militaristic Drinking, and the Rhetoric of Recovery -- 1. Very Drunken Episodes: Comedy TV's Discourses of Insobriety -- 2. "Drinking the War Away": Alcoholic Merriment in M*A*S*H and Other Military-Themed Sitcoms -- 3. The Big Book on the Small Screen: Alcoholics Anonymous, Standup Comedy, and Television's Road to Recovery -- Part Two. TV's Cult Imaginary: Comic Cultists, Pathologized Fandoms, and the Rhetoric of "Crazy" Talk -- 4. Very Crazy Episodes: Cultivating Misconceptions about Cults on American Television -- 5. "Drinking the Kool-Aid" of Cult TV: Fans, Followers, and Fringe Religions in Strangers with Candy and Veronica Mars -- Part Three. TV's Monstrous Imaginary: Comic Creeps, Neighborly Terrors, and the Rhetoric of Trump -- 6. Very Spooky Episodes: Intertextual Monsters, Moral Panics, and the Playful Perversions of Halloween TV -- 7. "Three-Headed Monster": Queer Representation, Social Class, and the Trumpist Rhetoric of Roseanne -- 8. "Ugly Americans": Animating Monsters, Demonizing Others, and Racializing Fear on American Television -- Beyond Bad and Evil: Finding TV's "Good Place"
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 27, 2023).
eBooks on EBSCOhost
Keywords: Television comedies -- United States -- History and criticism; Deviant behavior on television; Conduct of life on television; Comédies télévisées -- États-Unis -- Histoire et critique; PERFORMING ARTS / Television / History & Criticism; Deviant behavior on television; Conduct of life on television; Television comedies; United States; United States; Criticism, interpretation, etc; Television criticism and reviews; Television criticism and reviews; Critiques d'émissions télévisées.